Aerogels for water treatment: A review. (20th December 2021) - Ganesamoorthy, Ramasamy; Vadivel, Vinod Kumar; Kumar, Rajnish; Kushwaha, Omkar S.; Mamane, Hadas
Abstract: Numerous aerogels are available in the scientific literature, however very few of them are in the market. Silicon, polymer, and carbon-based aerogels are commercially applied in various applications as construction, transportation, coating, day-lightning, oil, and gas. For water remediation purposes, very few materials are commercially available as aerogel blankets used for oil adsorption. We present the use of aerogels as a platform to support a wide range of novel materials, such as metals, semiconductors, oxides, polymers, biopolymers, hybrids and carbon. Aerogels are porous, consisting of 90–99% air, and are assembled into nanostructured materials. The discussed topics include synthesis (sol–gel process, aging, drying [ambient pressure, freeze, supercritical]), aerogel-based materials for water treatment, water-purification applications for aerogels (oil and toxic organic pollutant cleanup, heavy metal ion removal), reactor design in a pilot-scale application, conclusions and outlook. Although the use of aerogels in point-of-use applications for water treatment is promising, there are gaps in the cost and implementation of these new materials. Improvement in manufacturing and reduction in production costs is required to enhance market availability. Hence, we emphasized reactor design for bulk synthesis purposes. This review critically discusses the scientific, technical, and common barriers to commercialization of these novel materials. Graphical abstract: Image 1 Highlights: Critical review on advances in aerogel preparation along with merits and demerits. Comprehensive summary on aerogel based materials for the water treatment applications. Discussion on importance of reactor design in aerogel scale up for water purification. Proposed flow diagrams for horizontal and vertical reactor design for pilot-scale.